The Effect of Nestle Product Bundling Sales Accompanied with Discounts and Gifts on the Increase in the Number of SKUs Sold in the Sales Area of PT Anugerah Bina Usaha Nusantara Lampung for the Period April to May 2024 - Raissa Kurnia Adha; Albari Albari (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to determine the effectiveness of Nestle's product bundling strategy, accompanied by discounts and prizes in increasing SKU (Stock Keeping Unit) sales at PT Anugerah Bina Usaha Nusantara in the General Trade and Alternative Trade distribution networks. The research method used in this study is qualitative with narrative analysis based on in-depth interview data with several related salesmen and SKU sales data before and after the implementation of the strategy. The results of the study indicate that the product bundling strategy is able to increase the average number of SKUs sold from 1-3 SKUs to 5-7 SKUs per store. In addition, this program has succeeded in expanding product distribution and overcoming limited purchasing patterns in stores through a combination of incentives such as discounts and prizes, accompanied by education on the benefits of purchasing product bundling to the store. However, the study also identified challenges such as store resistance to certain SKUs and limited flexibility in the amount of product bundling purchases. The findings of the study recommend that the company modify the strategy to be more flexible and sustainable, with periodic evaluations to avoid store dependence on promotions.